Enhancing Urban Drainage in Coastal Cities: A Simulation-Based Assessment of Nature-Based Solutions for Climate Resilience - Prihatin Timur; Alex Johnson; Emily Carter; Sofyan Dwi Laksana (Civil Engineering Science and Technology, 2025)
Climate change is now fully expressed through extreme rainfall and sea-level rise, and it is a major threat to coastal cities globally. Additionally, the exhaustion of urbanization makes the situation even more difficult. Conventional drainage systems are overburdened by the rising demand; thus, Nature-Based Solutions offer a way to build systemic resilience which is characterized by the restoration of natural hydrological functions. The main objective of this paper is to analyze the role of integrated NBS in the improvement of hydraulic performance in the drainage of tropical coastal cities. In this regard, we conduct a systematic literature review alongside scenario-based simulations using the Storm Water Management Model (SWMM) which is supplied with synthetic data that reflects a typical tropical coastal city. The findings suggest that a distributed network of bioswales, rain gardens, and permeable pavements may decrease the peak discharge and total runoff volume by 28.8% and 29.0% respectively, these changes involving to a great extent infiltration enhancement and time to peak delay. Hence, this research provides a quantifiable, conceptual basis that is applicable to the field of urban planners and engineers as a means of warranting the trend of NBS as an essential part of the living adaptations in jeopardized coastal urban zones.